The Cholinergic and Adrenergic Autocrine Signaling Pathway Mediates Immunomodulation in Oyster Crassostrea gigas - Liu, Zhaoqun; Wang, Lingling; Lv, Zhao; Zhou, Zhi; Wang, Weilin; Li, Meijia; Yi, Qilin; Qiu, Limei; Song, Linsheng (Frontiers in Immunology, 2018)
It is becoming increasingly clear that neurotransmitters impose direct influence on regulation of the immune process. Recently, a simple but sophisticated neuroendocrine-immune (NEI) system was identified in oyster, which modulated neural immune response via a “nervous-hemocyte”-mediated neuroendocrine immunomodulatory axis (NIA)-like pathway. In the present study, the de novo synthesis of neurotransmitters and their immunomodulation in the hemocytes of oyster Crassostrea gigas were investigated to understand the autocrine/paracrine pathway independent of the nervous system in oyster. After hemocytes were exposed to lipopolysaccharide (LPS) stimulation, acetylcholine (ACh) and norepinephrine (NE) in the cell supernatants both increased to a significantly higher level (2.71- and 2.40-fold, p < 0.05) comparing with that in the control group. The mRNA expression levels and protein activities of choline O-acetyltransferase (CgChAT) and dopamine β-hydroxylase (CgDBH) in hemocytes which were involved in the synthesis of ACh and NE were significantly elevated at 1 h after LPS stimulation, while the activities of acetylcholinesterase (CgAChE) and monoamine oxidase (CgMAO), two enzymes essential in metabolic inactivation of ACh and NE, were inhibited. These results demonstrated the existence of the sophisticated intracellular machinery for the generation, release and inactivation of ACh and NE in oyster hemocytes. Moreover, the hemocyte-derived neurotransmitters could in turn regulate the mRNA expressions of tumor necrosis factor (TNF) genes, the activities of superoxide dismutase (SOD), catalase (CAT) and lysosome (LYZ), and hemocyte phagocytosis. The phagocytic activities of hemocytes, the mRNA expressions of TNF and the activities of key immune-related enzymes were significantly changed after the block of ACh and NE receptors with different kinds of antagonists, suggesting that autocrine/paracrine self-regulation was mediated by transmembrane receptors on hemocyte. The present study proved that oyster hemocyte could de novo synthesize and release cholinergic and adrenergic neurotransmitters, and the hemocyte-derived ACh/NE could then execute a negative regulation on hemocyte phagocytosis and synthesis of immune effectors with similar autocrine/paracrine signaling pathway identified in vertebrate macrophages. Findings in the present study demonstrated that the immune and neuroendocrine system evolved from a common origin and enriched our knowledge on the evolution of NEI system.